Justice under Uncertainty - Elena Cettolin; Arno Riedl (Center for Economic Studies and ifo Institute (CESifo), 2013)
An important element for the public support of policies is their perceived justice. At the same time most policy choices have uncertain outcomes. We report the results of a first experiment investigating just allocations of resources when some recipients are exposed to uncertainty. Although, under certainty almost all uninvolved participants distribute resources equally, they exhibit remarkable heterogeneity in just allocations under uncertainty. Moreover, uninvolved participants allocate on average less to recipients exposed to higher degrees of uncertainty and allocations are correlated with their own risk preferences. The observed allocations are consistent with four different views of justice under uncertainty.
Keywords: C91; D63; 330; justice; uncertainty; experiment